Retinoblastoma - Ramasubramanian, Aparna; Shields, Carol L.; Tasman, William (New Delhi : Jaypee-Highlights, 2012)
Retinoblastoma is a rare type of cancer of the eye, often developing in early childhood, that affects the retina, the light sensitive tissue at the back of the eye that detects light and colour. This book is a step by step guide to all aspects of retinoblastoma. Beginning with sections on epidemiology, pathogenesis, genetics, clinical features, staging and diagnosis, the text then discusses different treatment therapies chemotherapy and radiation therapy. The final section explores supportive care including visual rehabilitation and psycho-social aspects, and future trends. With contributions from nearly 70 experts throughout the USA, Europe and Asia, this book contains 350 illustrative images and photographs. An appendix including chemotherapy regimens with appropriate dosage for children has been provided for quick reference
El retinoblastoma es un tipo raro de cáncer ocular que se desarrolla por lo general en la infancia y que afecta primariamente a la retina. Este libro es una guía paso a paso que abarca todos los aspectos de este tumor intraocular.
Section I. Epidemiology, pathogenesis and genetics Section II. Clinical features, staging and diagnosis Section III. Chemotherapy Section IV. Radiation Therapy Section V. Advanced retinoblastoma and systemic perspective Section VI. Pathology Section VII. supportive care and future trends
Keywords: RETINOBLASTOMA; TUMORES INTRAOCULARES; NEOPLASMAS DEL OJO; RETINOBLASTOMA